Designing dark tourism experiences: an exploration of edutainment interpretation at lighter dark visitor attractions. Issue 4 (4th July 2021) - Wyatt, Brianna; Leask, Anna; Barron, Paul
ABSTRACT: Existing dark tourism literature has explored various aspects of interpretation, including challenges in balancing interpretation efforts with concerns for historical accuracy, and managing ethical issues with interpreting past tragedies for packaged tourism purposes. However, research appears under-developed concerning the influences on the design of interpretation at dark visitor attractions, particularly those considered lighter due to their edutainment agenda. This paper thus critically explores the influences on the design of edutainment interpretation at three lighter dark visitor attractions, which are introduced as new attractions for study within dark tourism research. It also discusses the findings achieved that not only contribute to the study's conclusions and recommendations for future research in the realms of dark tourism and interpretation, but also contribute to enhancing interpretation design understanding for both dark tourism research and practice.